A Singular Initial-Value Problem for Second-Order Differential Equations - Afgan Aslanov (Abstract and Applied Analysis)
We are interested in the existence of solutions to initial-value problems for second-order nonlinear singular differential equations. We show that the existence of a solution can be explained in terms of a more simple initial-value problem. Local existence and uniqueness of solutions are proven under conditions which are considerably weaker than previously known conditions.